Analysis of CO2, CO, NO, NO2, and PM Particulates of a Diesel Engine Exhaust - Jamali, Q. B.; Bhatti, M. T.; Qazi, Q. A.; Kaurejo, B. H.; Qazi, I. A.; Solangi, S. H.; Jamali, A. S. (Engineering, Technology & Applied Science Research, 2019)
Exhaust emissions of a diesel engine are considered to be a substantial source of environmental pollution. Diesel engines are mainly used in vehicles and power generation. The usage of diesel engines is unavoidable as they give more power and performance, but at the same time, higher usage of diesel engines leads to increased air pollution, sound pollution, and emissions to the environment. Therefore, various attempts have been made to control the harmful emissions of engines. For this reason, different devices have been made such as catalytic convertors to overcome emission problems and purify the harmful gases. In order to meet these ends, a new system was designed that would contribute to controlling the air pollution of the engines. The system is also known as an aqua silencer, and its design is somehow different but still can be used as a silencer. The newly designed emission controller was installed in a test-bed diesel engine and a total of twenty experiments were conducted with and without the new emission controller at constant speed and at constant load. During these experiments, exhaust gases were analyzed with flue gas analyzers measuring CO2, CO, NO2, NO, and PM. The study concluded that the contaminants of diesel engine exhaust gases were) controlled by the developed emission controller.